Language and culture on the margins : global/local interactions - Kroon, Sjaak; Swanenberg, Adrianus Petrus Cornelis, 1968- (Routledge critical studies in multilingualism ;, 2018)
"This collection of thirteen essays examines sociolinguistic phenomena in a wide variety of marginal environments, providing both an overview of globalizaiton on the margins and a foundation for an expanded understanding of the processes of linguistic and cultural changes at work in these settings. Taking an expansive conceptual view of margins, the volume is organized in three parts, looking at examples of marginal spaces in the nation-state, in online environments, and in the peripheries of urban locations, globally to call attention to new and changing discursive genres, patterns, practices, and identities emerging in these spaces as a result of contemporary mobilities, the evolving global economy, and socio-political changes. With previous research previously confined to the study of globalization in urban areas, this volume opens the door for further research on the complex sociolinguistic processes resulting from globalization on the margins, making this an ideal resource for students and scholars in sociolinguistics, globalization and heritage studies, new media, anthropology, and cultural studies"--